2023
DOI: 10.1021/acs.jpcb.3c05900
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Pressure and Viscoelasticity of Antibodies and Their Correlation to Long-Term Stability in Formulation

Kiet G. Pham,
Benjamin R. Thompson,
Tingting Wang
et al.

Abstract: Monoclonal antibodies (mAbs) form viscoelastic gel-like layers at the air− water interface due to their amphiphilic nature, and this same protein characteristic can lead to undesired aggregation of proteins in therapeutic formulations. We hypothesize that the interfacial viscoelasticity and surface pressure of mAbs at the air−water interface will correlate with their long-term stability. To test this hypothesis, the interfacial viscoelastic rheology and surface pressure of five different antibodies with varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The rheological measurements of the protein molecules at long aging times are lower than what has been reported by the Furst and Wagner groups and are due to the upper limit that can be measured by our technique. 30,31 Thus, while the use of microscopic probes provides a great advantage over the techniques reported earlier in terms of detecting the initial stages in the evolution, either an active microrheology technique or rheometers with larger probes (like the ones used by Pham et al and Wood et al) would be needed to measure the moduli at longer times. 30,31 Furthermore, this passive microrheology technique is capable of not only measuring the average surface viscosity but also detecting local heterogeneities in the interfacial gel.…”
Section: Nist Mab Solutions In Pbs Buffermentioning
confidence: 99%
See 2 more Smart Citations
“…The rheological measurements of the protein molecules at long aging times are lower than what has been reported by the Furst and Wagner groups and are due to the upper limit that can be measured by our technique. 30,31 Thus, while the use of microscopic probes provides a great advantage over the techniques reported earlier in terms of detecting the initial stages in the evolution, either an active microrheology technique or rheometers with larger probes (like the ones used by Pham et al and Wood et al) would be needed to measure the moduli at longer times. 30,31 Furthermore, this passive microrheology technique is capable of not only measuring the average surface viscosity but also detecting local heterogeneities in the interfacial gel.…”
Section: Nist Mab Solutions In Pbs Buffermentioning
confidence: 99%
“…studied the response to the application of shear stress to a mAb film formed at the air–water interface and showed that the protein film formed a soft glass at the air–water interface . More recently, Pham et al also correlated the rheology of industrially relevant mAbs to their long-term stability under storage conditions . However, most of these rheological studies characterized the film after film formation, not during protein adsorption and film formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation